Odpowiedzi

2009-11-12T19:39:25+01:00
X ---> f(x ) = -1,2 x
f(x ) = -2,4
x =f(x) :(-1,2) = -2,4 :(-1,2) = 2
f(x) = -0,4
x = -0,4 :(-1,2) = 4/12 = 1/3
f(x) = 0
x = 0 :(-1,2) = 0
f(x) = 1,2
x = 1,2 :(-1,2) = -1
f(x ) = 1/5 = 0,2
x = 0,2 :(-1,2) = -1/6
Df ={-1; -1/6; 0; 1/3; 2} - dziedzina funkcji f.
Jest to funkcja malejąca.

2009-11-12T19:58:45+01:00
X ---> f(x ) = -1,2 x
f(x ) = -2,4
x =f(x) :(-1,2) = -2,4 :(-1,2) = 2
f(x) = -0,4
x = -0,4 :(-1,2) = 4/12 = 1/3
f(x) = 0
x = 0 :(-1,2) = 0
f(x) = 1,2
x = 1,2 :(-1,2) = -1
f(x ) = 1/5 = 0,2
x = 0,2 :(-1,2) = -1/6
Df ={-1; -1/6; 0; 1/3; 2} - dziedzina funkcji f.
Jest to funkcja malejąca.